Valkea kaupunki, mustat vedet Helsingin vedet 1800-luvun lopusta 2000-luvulle - Petri, Juuti (Tampere University Press, 2015)
White City, Black Waters is written by Adjunct Professor, PhD Petri S Juuti. The book examines how water and waste water services and water protection started and developed in Helsinki and Greater Helsinki area from late 1800s to the 2000s. Furthermore, it is discussed what are the challenges of the future looked from the point of view of the professionals of the water sector.